Provisions of mahar (dowry) in Islam practiced by the Prophet Muhammad and his companions are substantially used as a standard of giving dowry in a marriage. Mahar provided by the Prophet as well as those by his companions had a high economic value; unless they were fortuneless. However, what has been practiced by many recently does not reflect the deed of the Prophet Muhammad. Nowadays, people tend to provide a set of prayer outfit as a mahar, an item which could not support a family financiall - Yenti, Endri; Busyro, Busyro; Ismail, Ismail; Rosman, Edi; Wadi, Fajrul (Al-Risalah, 2020)
Provisions of mahar (dowry) in Islam practiced by the Prophet Muhammad and his companions are substantially used as a standard of giving dowry in a marriage. Mahar provided by the Prophet as well as those by his companions had a high economic value; unless they were fortuneless. However, what has been practiced by many recently does not reflect the deed of the Prophet Muhammad. Nowadays, people tend to provide a set of prayer outfit as a mahar, an item which could not support a family financially. Even if some people do provide high-priced mahar, yet much of it is used before akad (the marriage vow) to finance a wedding reception, rather than handing out the money directly to the wife. This article aims at evaluating this tradition, since it discriminates against women’s privilege of mahar. From the findings of the research, it is concluded that traditions; giving a set of prayer outfit to women, or using mahar as a payment for a wedding reception discriminate against women’s rights because the essence of mahar is to economically support or help the wife in the future. According to the provisions of ʻurf, this tradition does not fit in the Islamic law and is not legitimate to be incorporated into the Archipelago’s fiqh.